Liposome induction of CD8+ T cell responses depends on CD169+ macrophages and Batf3-dependent dendritic cells and is enhanced by GM3 inclusion - Grabowska, J. (Elsevier B.V., 2022)
10.1016/j.jconrel.2021.01.029